2013
DOI: 10.1007/s00134-013-2857-4
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction models for pediatric intensive care: comparison of overall and subgroup specific performance

Abstract: All models discriminated well, also in most subgroups including neonates, but had difficulties predicting mortality for patients >6 days at the PICU. In a western European setting both the PIM2(-ANZ06) or a recalibrated version of PRISM3-24 are suited for overall individualized risk prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 28 publications
1
41
1
1
Order By: Relevance
“…Visser et al reported that PIM2 showed a tendency to predict lower mortality than that observed in the younger patients [30]. Ciofi degli Atti also reported an inadequate calibration of the score in adolescents.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Visser et al reported that PIM2 showed a tendency to predict lower mortality than that observed in the younger patients [30]. Ciofi degli Atti also reported an inadequate calibration of the score in adolescents.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Reasons for ICU admission were grouped into respiratory distress/failure, hemodynamic instability and others. The Pediatric Index of Mortality 2 (PIM 2) score was used as the measure of illness severity at ICU admission and calculated retrospectively [18,19]. Respiratory failure was defined as the need for respiratory support (non-invasive or invasive ventilation), and shock was defined as need for vasopressor support (other than dopamine B5 mcg/kg/min) during the initial 24 h of admission.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…Área bajo la curva ROC= 0,8392. et al 20 evaluaron el funcionamiento de ambos puntajes y sus distintas versiones en un estudio multicéntrico en Dinamarca y encontraron que todos los modelos calibraron en forma adecuada para los pacientes egresados de la UCIP durante los primeros 6 días. En cambio, la mortalidad observada fue significativamente mayor que la predicha (RME > 1) en pacientes con estadía superior.…”
Section: 00unclassified